2016
DOI: 10.15436/2377-0619.16.044
|View full text |Cite
|
Sign up to set email alerts
|

Concept to Sale of a Healthier Snack Bar

Abstract: Snacking between meals provides an important contribution to dietary intake of key nutrients. There is a need for snack bars that are nutrient dense, have a low glycemic load and increase feelings of fullness and satiety. Over the last three years a branded "Nothing Else" dates and almonds life saver snack bar, without preservatives or additives, has been developed in partnership with a food manufacturer. In June 2015 the final bar, with eight simple ingredients, was first produced by our industry partner to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In partnership with a food manufacturer who baked and packaged the bars, design expertise for the food label from within the university and monitoring of sales through the food outlets at the Auckland University of Technology it has shown that the bar is commercially viable [52]. The Nothing Else™ bar has a favorable effect on acute glycemic response and satiety [53].…”
Section: Potential Strategies To Improve Nutrition and Reduce Riskmentioning
confidence: 99%
“…In partnership with a food manufacturer who baked and packaged the bars, design expertise for the food label from within the university and monitoring of sales through the food outlets at the Auckland University of Technology it has shown that the bar is commercially viable [52]. The Nothing Else™ bar has a favorable effect on acute glycemic response and satiety [53].…”
Section: Potential Strategies To Improve Nutrition and Reduce Riskmentioning
confidence: 99%
“…In this field study, we aimed to examine whether offering the newly developed healthy and attractive snack with a correspondingly branded food truck would make people buy and eat the snack. The branding was added to give the snack a professional look, since the appearance of food is an important factor in marketing [ 47 ]. The effects of our intervention were measured by the volume of snack sales and by responses to questions about how much people liked the snack and the food truck branding.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, available snacks are not formulated to meet the specific nutrient requirements of pregnant women, especially in food cravings related to undesirable excessive weight gain during pregnancy (Blau et al, 2020). Instead, they usually have high energy, fat, and sugar (Rush et al, 2016). Snack bars are usually made using a base of grains or protein and enriched with a wide range of nutrientrich ingredients, vitamins, minerals, and herbs (Constantin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%